The Survivors: Self-Determination and How It Helps Youngsters to Face the Challenges at the Work Place - Maria Kristina Salelatu (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
As a screenplay project about youngsters’ work life, The Survivors follows a story of three young interns named Clara, Sebastian, and Bakti in their journey during the internship program held by a famous e-commerce company. Having not enough experience working in a company, the interns have a hard time to survive in the company. Moreover, they also have non-work related problems. Luckily, these interns later learn about Self-Determination. Being self-determined means that the interns can intrinsically motivate themselves, do things by their own initiative, and also decide things based on their moral or values. Using Deci & Ryan’s Self Determination Theory in work life context, the creative work shows the importance of self-determination in facing the challenges at the work place and how youngsters can actually gain self-determination. The genre is Dramedy as it shows what usually happens to youngsters in a work place then filled it with humors so that it can be entertaining. Keywords: Youngsters, The Survivors, Dramedy, Internship, Work Life, Work Place